A Case of Abdominal Cocoon Syndrome: A Rare Cause of Small Bowel Obstruction At Aber Hospital in Northern Uganda - Ssewanyana, Yasin; Ssekitooleko, Badru; Daniel, Ongaro; Omona [PhD], Kizito (International Journal of Medicine, 2021)
Abdominal cocoon syndrome (ACS) is a rare cause of small bowel obstruction characterized by partial or complete encasement of small bowel loops in a thick fibro-collagenous sac. It poses diagnostic difficulties due to the non-specific nature of its presentation and thus in most cases, diagnosed incidentally at laparotomy.The researchers present a case of a 27-year old female Ugandan who presented to a rural hospital in Northern Uganda with complaints of central abdominal pain, failure to pass stool and bilious vomiting for three days. She also had feelings of a peri-umbilical mass. She had several episodes of related obstructive symptoms that would be self-limiting for a year. She had unremarkable past surgical, past medical and past gynecological history. Laboratory investigations were unremarkable.Preoperative diagnosis of small bowel intussusception was made basing on examination and ultrasonography report and the patient was managed operatively. At laparotomy, almost all the small bowel loops were found encased in a thick, whitish, fibrous membrane. There was also marked inter-loop adhesions. The membranous sac was incised and completely removed using both sharp and blunt dissection. Inter-loop adhesions were released solely by blunt dissection.The patient recovered postoperatively and was discharged on the seventh postoperative day.Â Â
Keywords: Abdominal Cocoon Syndrome; Small Bowel Obstruction; Laparotomy; Intussusceptions.